Whole genome population structure of North Atlantic kelp confirms high‐latitude glacial refugia - Trevor T. Bringloe; Antoine Fort; Masami Inaba; Ronan Sulpice; Cliodhna Ní Ghriofa; Agnes Mols‐Mortensen; Karen Filbee‐Dexter; Christophe Vieira; Hiroshi Kawai; Takeaki Hanyuda; Dorte Krause‐Jensen; Birgit Olesen; et al. (Molecular Ecology, 2022)
Coastal refugia during the Last Glacial Maximum (~21,000 years ago) have been hypothesized at high latitudes in the North Atlantic, suggesting marine populations persisted through cycles of glaciation and are potentially adapted to local environments. Here, whole‐genome sequencing was used to test whether North Atlantic marine coastal populations of the kelp Alaria esculenta survived in the area of southwestern Greenland during the Last Glacial Maximum. We present the first annotated genome for A. esculenta and call variant positions in 54 individuals from populations in Atlantic Canada, Greenland, Faroe Islands, Norway and Ireland. Differentiation across populations was reflected in ~1.9 million single nucleotide polymorphisms, which further revealed mixed ancestry in the Faroe Islands individuals between putative Greenlandic and European lineages. Time‐calibrated organellar phylogenies suggested Greenlandic populations were established during the last interglacial period more than 100,000 years ago, and that the Faroe Islands population was probably established following the Last Glacial Maximum. Patterns in population statistics, including nucleotide diversity, minor allele frequencies, heterozygosity and linkage disequilibrium decay, nonetheless suggested glaciation reduced Canadian Atlantic and Greenlandic populations to small effective sizes during the most recent glaciation. Functional differentiation was further reflected in exon read coverage, which revealed expansions unique to Greenland in 337 exons representing 162 genes, and a modest degree of exon loss (103 exons from 56 genes). Altogether, our genomic results provide strong evidence that A. esculenta populations were resilient to past climatic fluctuations related to glaciations and that high‐latitude populations are potentially already adapted to local conditions as a result.

Association Between Lifetime Cadmium Intake and Cadmium Concentration in Individual Urine - E. Kobayashi; Y. Suwazono; M. Uetani; T. Inaba; M. Oishi; T. Kido; H. Nakagawa; K. Nogawa (Bulletin of Environmental Contamination and Toxicology, 2005)

C-terminal peptides of p53 molecules enhance radiation-induced apoptosis in human mutant p53 cancer cells - K. Ohnishi; H. Inaba; J. Yasumoto; K. Yuki; A. Takahashi; T. Ohnishi (Apoptosis, 2004)

Identification of 142 single nucleotide polymorphisms in 41 candidate genes for rheumatoid arthritis in the Japanese population - Y. Ohnishi; K. Suematsu; M. Minami; T. Seki; M. Yukioka; O. Saiki; R. Teshima; O. Kudo; K. Ishikawa; A. Ueyosi; H. Tateishi; M. Inaba; et al. (Human Genetics, 2000)

Identification of 142 single nucleotide polymorphisms in 41 candidate genes for rheumatoid arthritis in the Japanese population - R. Yamada; T. Tanaka; Y. Ohnishi; K. Suematsu; M. Minami; T. Seki; M. Yukioka; A. Maeda; N. Murata; O. Saiki; R. Teshima; O. Kudo; et al. (Human Genetics, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Appearance of slow-reacting, complement-requiring hemagglutination-inhibiting antibody in swine infected with pseudorabies virus - Y. Inaba; N. Tetsu; H. Toriyoshi; M. Yukawa; K. Yoshiki; T. Hirahara; A. Izumida (Archives of Virology, 1990)

Hemagglutination with pseudorabies virus - N. Tetsu; Y. Inaba; M. Yukawa; K. Yoshiki; T. Hirahara; Y. Furuya; S. Ito; A. Yonemochi; H. Ishikawa (Archives of Virology, 1989)

Hemagglutination with transmissible gastroenteritis virus - M. Noda; H. Yamashita; F. Koide; K. Kadoi; T. Omori; M. Asagi; Y. Inaba (Archives of Virology, 1987)

Hemagglutination with ovine rotavirus - T. Makabe; M. Sato; S. Ouneda; Y. Inaba (Archives of Virology, 1986)

Isolation of ovine rotavirus in cell cultures - T. Makabe; H. Komaniwa; Y. Kishi; K. Yataya; H. Imagawa; K. Sato; Y. Inaba (Archives of Virology, 1985)

Hemagglutination of epizootic hemorrhagic disease virus - S. Tokuhisa; Y. Inaba; Y. Miura; K. Sato; H. Akashi; T. Tsuda; I. Shibata (Archives of Virology, 1981)

Isolation of human rotavirus in cell cultures - K. Sato; Y. Inaba; T. Shinozaki; R. Fujii; M. Matumoto (Archives of Virology, 1981)

Replication of bovine coronavirus in cell line BEK-1 culture - Y. Inaba; K. Sato; H. Kurogi; E. Takahashi; Y. Ito; T. Omori; Y. Goto; M. Matumoto (Archives of Virology, 1976)

Epizootic congenital arthrogryposis-hydranencephaly syndrome in cattle: Isolation of Akabane virus from affected fetuses - H. Kurogi; Y. Inaba; E. Takahashi; K. Sato; T. Omori; Y. Miura; Y. Goto; Y. Fujiwara; Y. Hatano; K. Kodama; S. Fukuyama; N. Sasaki; et al. (Archives of Virology, 1976)

Serologic evidence for etiologic role of Akabane virus in epizootic abortion-arthrogryposis-hydranencephaly in cattle in Japan, 1972?1974 - H. Kurogi; Y. Inaba; Y. Goto; Y. Miura; H. Takahashi; K. Sato; T. Omori; M. Matumoto (Archives of Virology, 1975)

Neutralizing antibody against Akabane virus in precolostral sera from calves with congenital arthrogryposis-Hydranencephaly syndrome - Y. Miura; S. Hayashi; T. Ishihara; Y. Inaba; T. Omori; M. Matumoto (Archives of Virology, 1974)

Bovine respiratory syncytial virus: Host range in laboratory animals and cell cultures - M. Matumoto; Y. Inaba; H. Kurogi; K. Sato; T. Omori; Y. Goto; O. Hirose (Archives of Virology, 1974)

Isolation of rhinovirus from cattle in outbreaks of acute respiratory disease - H. Kurogi; Y. Inaba; Y. Goto; A. Takahashi; K. Sato; T. Omori; M. Matumoto (Archives of Virology, 1974)

Vaccination of cattle against bovine ephemeral fever with live attenuated virus followed by killed virus - Y. Inaba; H. Kurogi; A. Takahashi; K. Sato; T. Omori; Y. Goto; T. Hanaki; M. Yamamoto; S. Kishi; K. Kodama; K. Harada; M. Matumoto (Archives of Virology, 1974)

New serotypes of reoviruses isolated from cattle - H. Kurogi; Y. Inaba; E. Takahashi; K. Sato; Y. Goto; T. Omori; M. Matumoto (Archives of Virology, 1974)

Structure of bovine respiratory syncytial virus - Y. Ito; Y. Tanaka; Y. Inaba; T. Omori (Archives of Virology, 1973)

Electron microscopy of Ibaraki virus - Y. Ito; Y. Tanaka; Y. Inaba; T. Omori (Archives of Virology, 1973)

Isolation and properties of bovine parvovirus type 1 from Japanese calves - Y. Inaba; H. Kurogi; E. Takahashi; K. Sato; Y. Tanaka; Y. Goto; T. Omori; M. Matumoto (Archives of Virology, 1973)

Formalin-inactivated, aluminum phosphate gel-adsorbed vaccine of bovine ephemeral fever virus - Y. Inaba; H. Kurogi; K. Sato; Y. Goto; T. Omori; M. Matumoto (Archives of Virology, 1973)